Lengthening Patients Previously Treated for Massive Lower Limb Reconstruction for Bone Tumors with the PRECICE 2 Nail - Laura Campanacci; Luca Cevolani; Marco Focaccia; Giovanni Luigi Di Gennaro; Barbara Dozza; Eric Staals; Federica Zuccheri; Giuseppe Bianchi; Davide Maria Donati; Marco Manfrini (MDPI AG, 2023)
The objective of this study was to determine the efficacy of the PRECICE 2® nail in the treatment of lower limb length discrepancy in patients with a history of bone tumors. This study reports on outcomes, complications, and the safety of the PRECICE 2 limb lengthening nail in a cohort of pediatric patients with limb length discrepancy after surgery for bone tumors. Seventeen patients were treated with intramedullary magnetic nails. The average patient age at the time of surgery was 19 (range 11-32). The PRECICE 2 nail was used on 14 femurs (6 retrograde and 8 anterograde) and 3 tibias. The average consolidation time was 141 days (range 50-360) with a mean CI of 31 ± 12 days/cm. The ASAMI bone score showed 14 (82%) excellent results, 1 (6%) good result, and 2 (12%) poor results. The ASAMI functional score showed 13 (84.6%) excellent results, 3 (11.5%) good results, and 1 (3.8%) fair result. Patients treated with chemotherapy for bone cancer did not show any increase in distraction time or consolidation time. A total of 3 (17%) problems, 1 obstacle (5.5%), and 1 complication (5.5%) were encountered in our case series. The PRECICE 2 nail allows for effective and accurate lengthening preserving the range of motion in patients treated for bone tumors.